The Increase of Financial Performance in Mediate the Good Corporate Governance Toward the Company’s Value - Kartika, Andi; Sudarsi, Sri; Nuswandari, Cahyani (Jurnal Penelitian Ekonomi dan Bisnis, 2022)
The research aims to testine empirically the effect of good corporate governance through the managerial ownership, the independent commissioner, and the audit committee toward the company’s value with the financial performance as the mediation variable. The population in this research is manufactur companies that has registered on BEI, with using the purposive sampling technique. The method that used on this research is path analysis.The result of this research shows that a good corporate governance through the managerial ownership, the independent commissioner, and the audit committee is able to increase the company’s financial performance. The managerial ownership does not has any effect to the company’s value, while the independent commissioner, the audit committee, and the financial performance has positive effects to the company’s value. The financial performance can mediate between independent commissioner to the company’s value. The financial value will not be a mediation’s variable between the audit committee to the company’s value.Keywords:Managerial ownershipIndependent commissionerAudit committeeFinancial performanceThe company’s value